Unawareness of the disease in patients with schizophrenia: diagnosis and insight-oriented psychotherapy - Osokina, O. I.; Ivnyev, B. B.; Putyatin, G. G.; Denisov, Ye. M.; Ushenin, S. G. (Zaporozhye Medical Journal, 2018)
Relevance. Phenomenon of patients' unawareness of their illness (insight) is a pathognomonic diagnostic criterion that distinguishes schizophrenia from many other psychiatric disorders. More than half of patients with schizophrenia do not realize their illness that makes their treatment more difficult. Diagnosis of insight in patients with schizophrenia is an important issue. The volume and content of rehabilitation programs depends on it. The purpose of research is to study the structure of insight in patients with schizophrenia, its relationship with certain clinical, social and psychological indicators, and to assess the influence of insight-oriented psychotherapy on the outcomes of schizophrenia. Material and methods. 237 patients with schizophrenia were studied: 139 (58.6 %) men and 98 (41.4 %) women aged 18-35 years. Patients of the main group (122 people) received pharmacotherapy and were included in the program of insight-oriented psychotherapy. Patients of the comparison group (115 people) received standard treatment. Measurement of the insight level was carried out using the scale of unawareness of mental disorder (SUMD). To study social indicators the scale of social functioning in various spheres was used (Zaitsev, 1999). The quality of life level and social stigma were measured by WHOQOL-BREF and adapted version of the self-stigmatization scale (SSMIS). Evaluation of outcomes in schizophrenia was carried out using the IMR and RMQ scales. The level of cognitive functioning was assessed by the GACF-CogFu scale. The severity of depression was measured by the scale developed by Beck (BDI). The mechanisms of psychological defense were assessed using the scale of R. Plutchik, H. Kellerman (1979). Mathematical processing of the results was also carried out. Results. Correlations were found between a higher level of patient awareness of the disease and its better prognosis (r= -0.507; p<0.05), a higher level of social functioning (r= 0.478; p<0.05), quality of life (r= -0.311; p<0.05), cognitive functioning (r= -0.508; p<0.05) and a lower intensity of defensive psychological mechanisms (r= -0.401; p<0.05). A different predictive value of some insight components was found. There were detected correlations between a successful disease prognosis and a high degree of patient awareness of the disease symptoms (r = -0.318; p<0.05), the need for treatment (r = -0.603; p<0.05), the drug effect (r = -0.312; p<0.05) and a low awareness level of how people perceive the patient’s illness (r = 0.527; p<0.05) and its social consequences (r= 0.419; p<0.05). The highest association with the risk of depressive symptoms and self-stigmatization had the following insight components: awareness of the mental illness presence (r= -0.365 and r= -0.525, respectively; p<0.05) and perception by others (r= -0.654 and r= -0,417; p<0.05), awareness of the diagnosis (r= -0.312 and r= -0.45; p<0.05), social consequences of the disease (r= -0.3 and r= -0.621; p<0.05) and their perception by others (r= -0.531 and r= - 0.576; p<0.05). Conclusions. Insight-oriented psychotherapy has proven effective in patients with schizophrenia treatment. It is reasonable to increase the patients' awareness of the disease symptoms, their causes, the need for treatment and the effectiveness of medicines, while leaving intact those aspects of insight that increase the risk of depression, psychological distress and self-stigmatization.